PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN SERTA DAMPAKNYA PADA LOYALITAS KONSUMEN PRODUK APPLE DI BANDA ACEH - Edward Edward; Syafruddin Chan; M. Shabri Abdul Majid (Departemen Manajemen, Universitas Syiah Kuala, 2017)
ABSTRACT One of the marketing element that affect consumer behavior is the combination of product management and promotion mix. Apple is one big company that has many users and they are very loyal. But due to lack of innovation, then the loyalty of its users were also reduced. Banda Aceh as one of the regional markets in Indonesia surprisingly placed Samsung was in first rank in mobile phone brand loyalty for the first time. This is quite surprising considering Samsung is able to defeat the famous Apple that has a strong user base, loyal, and fanatical, but in fact, Samsung has a bigger share of the market. The population used in this study is the people who use Apple products in Banda Aceh City. This study the number of samples used is 120 people . Hypothesis testing was done by using indicators CR and P. Because of the 9 hypothesis tested in this study have CR value above 1.96 or P value smaller than 0.05, Then all hypotheses tested reject Ho and accept H1. In other words the independence and intervening variables have the effect of increasing the dependent variable if only the independent variables and the intervening can be improved by Apple product manufacturers Keywords: Promotional Mix, Consumer Satisfaction, Customer Loyalty of Apple product users in Banda Aceh